Strategies for building a successful ultrasound guided FNA practice in department of pathology—Experience at a university hospital. Issue 10 (11th July 2017) - Wu, Maoxin; Shroyer, Kenneth R.
Abstract: Introduction: Although pathology services focused on fine needle aspiration (FNA) biopsy of superficial palpable masses with on‐site cytological evaluation are available in a wide range of clinical and academic settings, the addition of ultrasound (US) guidance into FNA practice by a cytopathologist group can be challenging. An US‐FNA service provided by a cytopathologist in the department of Pathology is a relatively new practice in the field of medicine. This report summarizes our experience and strategies in achieving this objective and our successful preliminary results. Materials and Methods: The US‐FNA service includes (1) an FNA procedure to be performed by a cytopathologist under US guidance; (2) onsite adequacy evaluation and diagnosis to be done by the same cytopathologist; and immediate patient consultation and sample triaging carried out by the same cytopathologist in an FNA suite within the department of Pathology. The FNA suite including a procedure room equipped with a portable US machine, an exam/procedure table, a mobile cabinet with FNA supplies, a counter with sink, and a reception room with waiting area is set‐up. Results: The establishment of the US‐FNA service is successful. There is an incremental growth of the service over the first 8 months. Among the 114 cases performed during the first 8 months, the case type distribution is shown to be 50% thyroid nodules, 33% lymph nodes, 5.5% salivary gland masses, 3.5% breast masses, and 8% soft tissue masses. Conclusions: The authors' initial 8 months experience and strategies in setting up a new US‐FNA practice in a new institution are discussed to highlight obstacles encountered and approaches that promoted the successful establishment of a new service. A conservative approach, focusing on building partnerships with existing clinical services, can be successfully implemented in most institutions, if appropriate strategies are applied. The main strategy is to ensure that the best interests of patients remain the primary focus and that everything possible is done to improve the quality and effectiveness of patient care by providing the best possible diagnostic US‐FNA service, to enable optimal clinical management.